Social security as a field of Euroregional cooperation. Deliberations on the example of the activity of the Euroregion “Beskidy” - Sanetra-Półgrabi, Sabina; Sapiński, Aleksander (Social Development and Security, 2021)
The main aim of this article is to present the concept of the Euroregion as a platform for cooperation in the area of social security. The issue itself needs to be constantly updated not only because of the constant challenges facing the European Union and other countries. The outlook character of the article presents a view on the importance of cooperation between self-government administration bodies and other subjects of economic life for the development of cooperation within the Euroregions. The article mainly focuses on the fight against often negative stereotypes and undertakings whose task is to increase the standard of economic life by increasing activities aimed at improving the quality of Euroregional cooperation. The Euroregion "Beskidy" was selected for the study, which is diverse in ethnic, sociological, historical, but also economic and social terms. Its unique features have allowed the authors to more clearly emphasize the message of the article. Tourism and its international, Euro-regional character is also an important element of cooperation. In order to carry out the research that resulted in this article, the methods of researching the sources sucked in in terms of critical analysis of literature were used, as well as juxtaposing them with the previously conducted research on Euroregions and safety by the authors. On the basis of the analysis, the article presents a significant contribution of social integration and cross-border cooperation to the development of the Euroregion as well as to the development of social security as a non-military part of the research topic. The creation of new types of innovative pro-social undertakings opens up the Euroregions, and thus the Member States to further internal integration and intensification of activities to strengthen socio-economic cooperation with neighbouring countries.